Analyzing the Impact of Non-Performing Loans and Loan-to-Deposit Ratios on Return on Assets: A Study of Conventional Commercial Banks in Indonesia - Wahyuni, Wahyuni; Badollahi, Ismail; Nurhidayah, Nurhidayah; Mardiastuti, Wahyu (Advances in Management & Financial Reporting, 2023)
The objective of this study is to examine the impact of non-performing loans (NPL) and loan-to-deposit ratios (LDR) on return on assets (ROA) within the time frame of 2015 to 2019, specifically focusing on conventional commercial banks that are publicly listed on the Indonesia Stock Exchange. The research conducted in this study is categorized as explanatory. The data utilized for analysis is quantitative and is derived from secondary sources, specifically the financial reports of conventional banks that are publicly listed on the Indonesia Stock Exchange. The present study used a data analysis technique known as multiple linear regression and partial and simultaneous tests, utilizing the statistical software SPSS version 22. The findings of the research indicate that there is a substantial negative relationship between non-performing loans (NPL) and return on assets (ROA), while the relationship between loan-to-deposit ratio (LDR) and return on assets (ROA) is negative but not statistically significant. Concurrently, the non-performing loan (NPL) and loan-to-deposit ratio (LDR) exert a substantial influence on the return on assets (ROA).